EFEKTIVITAS HERBISIDA PARAQUAT DIKLORIDA 140 G/L TERHADAP PENEKANAN GULMA, PERTUMBUHAN, DAN HASIL JAGUNG (Zea mays L.) - Yayan Sumekar; Dedi Widayat; Ika Aprillia (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2021)
Maize (Zea mays L.) is one of the cereal group's commodities with high economic value because of its position as the main source of carbohydrates and protein after rice. The problem that often occurs in maize cultivation and greatly affects maize productivity is weeds. Chemical weed control using herbicides in large crop areas can be the right choice because it can save production costs and reduce damage to soil structures. Paraquat dichloride herbicide is a non-selective contact herbicide, which has the characteristic that when exposed to sunlight the herbicide molecules react to produce hydrogen peroxide which damages cell membranes and all plant organs, causing the plant to burn. This herbicide can control grass and broadleaf weeds. The research conduct from March - July 2020 at the Ciparanje experimental field, Faculty of Agriculture, Padjadjaran University. The treatment design used a Randomized Block Design (RBD) with 7 treatments, namely: Paraquat dichloride 140 g/l at a dose 1.00 l/ha; Paraquat dichloride 140 g/l dose 1.25l/ha; Paraquat dichloride 140 g/l dose 1.50 l/ha; Paraquat dichloride 140 g/l dose 1.75 l/ha; Paraquat dichloride 140 g/l at a dose of 2.00 l/ha; Manual Weeding; Control (No Treatment). The difference in trials using the F test and tested using the Duncan test at the 5% real level. The results showed that applying the herbicide Paraquat dichloride 1.00 l/ha - 2.00 l/ha could control weeds in maize cultivation up to 6 weeks after application and positively affect the growth yield of maize.